2023
DOI: 10.1007/s00223-023-01155-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, Immunological, Dietary, Gut Microbiota, and Environmental Determinants of Osteoporosis in the Course of Celiac Disease: Which Factor Plays the First Violin in This Orchestra?

Kinga Skoracka,
Szymon Hryhorowicz,
Francesco Tovoli
et al.

Abstract: Celiac disease (CD) is a chronic small intestinal immune-mediated enteropathy precipitated by exposure to dietary gluten in genetically predisposed individuals. The worldwide prevalence of CD is estimated to be 0.7–1.4% of the general population. Etiopathology of this disease is multifactorial, with genetic determinants being a major contributing player to CD susceptibility. Its manifestation embraces different organs, including the musculoskeletal apparat. Patients with CD have increased risk of bone disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…In a group of 250 patients from the Netherlands, at CeD diagnosis, osteoporosis and osteopenia were found in 23% and 35%, respectively [ 49 ]. Skoracka et al proposed that genetic, immunological, dietary, and environmental factors as well as unfavorable gut microbiota may be responsible for the development of osteoporosis [ 50 ]. One study reported that Caucasian adults with symptoms/signs of undiagnosed CeD in the early years of life showed foreheads larger than those of CeD patients with an onset of CeD later in life [ 51 ].…”
Section: Bonesmentioning
confidence: 99%
“…In a group of 250 patients from the Netherlands, at CeD diagnosis, osteoporosis and osteopenia were found in 23% and 35%, respectively [ 49 ]. Skoracka et al proposed that genetic, immunological, dietary, and environmental factors as well as unfavorable gut microbiota may be responsible for the development of osteoporosis [ 50 ]. One study reported that Caucasian adults with symptoms/signs of undiagnosed CeD in the early years of life showed foreheads larger than those of CeD patients with an onset of CeD later in life [ 51 ].…”
Section: Bonesmentioning
confidence: 99%